EXPERIMENTAL RESULTS ON MIXING GRANULAR MATERIALS IN VIBRATION MIXER - William D. ILCHENKO; Natalia V. GUCHEVA (Advanced Engineering Research)
The results of experiments on calculating energy for vibration mixing of bulk materials are presented. Dependence of the mixing energy on the vibration parameters and mechanical properties of the material is determined on the basis of Carnot theorem on inelastic impact.